Intermediate uveitis: an unusual presentation of cytomegalovirus intraocular infection in an immunocompetent patient. (12th May 2015) - Amin, Rowayda M; Ostheimer, Trucian; Butler, Nicholas J
Abstract : We report a case of cytomegalovirus (CMV) intraocular infection in an otherwise healthy 51-year-old patient, presenting atypically as isolated intermediate uveitis without retinitis or retinal vasculitis. The patient had a confirmed CMV infection as a cause of her intraocular inflammation via PCR DNA testing of an aqueous sample. Appropriate oral antiviral therapy was initiated, and resulted in complete resolution of inflammation and improvement in visual acuity. Prophylactic therapy was instituted thereafter.